Enhancing acetaminophen removal through persulfate activation with ZnCl2-SPI biochar: A study on reactive oxygen species contribution according to acetaminophen concentration - Yang, Heejin; Choi, Gyu Ri; Jae Jeong, Yoo; Cho, In Sun; Park, Seong Jik; Lee, Chang Gu (Chemical Engineering Journal, 2024)
This study investigated the effect of acetaminophen (ACP) removal through the ZnCl2-SPI/persulfate process and evaluated the production of reactive oxygen species (ROS) based on ACP concentration. ACP removal efficiency reached 96 % within 5 min, regardless of the initial concentration (40 μM and 200 μM). The change in pH had a minimal effect on the removal efficiency, and the reactivity improvement increased the removal rate at pH 4 and 10. The persulfate-to-ACP ratio significantly influenced ACP removal, with the minimum ratio required for effective ACP removal being 5. The scavenger test results showed that the effect of O2•− radicals prevailed when ACP concentration was 40 μM, whereas the effect of 1O2 prevailed when ACP concentration was 200 μM. This indicates that ROS contribution depends on the persulfate-to-ACP ratio. When this ratio was high, ZnCl2-SPI and persulfate reacted to generate O2•− radicals via the radical pathway. Conversely, when this ratio was low, ACP and persulfate reacted to generate 1O2 via the nonradical pathway. The difference in these mechanisms was analyzed through electrochemical analysis, confirming that ACP and persulfate reacted via a coupling effect. In conclusion, the ROS generated in the ZnCl2-SPI/persulfate process varied depending on the persulfate-to-ACP ratio, and the ROS generation path can be selectively controlled by adjusting this ratio.
Keywords: Biochar; Initial concentration; Micro-algae; Microalga biochar; Minimal effects; Persulfate activations; Persulphate; Reactive oxygen species; Removal efficiencies; Selective pathway; Microalgae biochar; Persulfate activation; Pharmaceuticals; Polymerization; Selective pathway